Tinjauan Yuridis Penyelesaian Eksekusi Hak Tanggungan Melalui Pengadilan Negeri (Studi Di Pengadilan Negeri Boyolali) - PERKASA, ALVIN DHADY RAJAWALI, Darsono, S.H, M.H (2017)
One way of execution given in Act No. 4 of 1996 on Mortgage is the execution path based on the certificate of title executorial Mortgage conducted with the assistance of the court. In this paper the author tries to provide an analysis of executing the Mortgage object with the help of the court in Boyolali District Court. Execution is the realization of the obligations of the parties defeated in the judge's decision, in order to meet the achievements listed in the judge's decision was legally binding. The execution procedure security rights in court through several stages including the petition, granting aanmaning, implementation of the foreclosure auction execution and determination of execution. Obstacles in the execution of a security interest in Boyolali District Court, among which the third party of resistance, the resistance of the debtor or executed during the execution of confiscation execution by the Court and the absence of buyer or buyers.